2015
DOI: 10.1002/ctpp.201400104
|View full text |Cite
|
Sign up to set email alerts
|

Pressure‐Driven Enthalpic and Lifshitz Transition in 122‐Pnictides

Abstract: Iron-arsenic pnictides are a class of compounds in which strong Coulomb interactions manifest in novel properties. We discuss basic ideas behind a Lifshitz transition and review salient properties of 122-pnictides (AFe 2As2; A = Ca, Sr, Ba, Ra). Using T = 0 first principles total energy calculations, as a function of hydrostatic pressure, we show that several pressure-driven anomalies, and the tetragonal (T) to collapsed tetragonal (cT) phase transition in the 122-pnictides family, can be understood as consequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…The theory predicted the transition to the zero-magnetic moment at the cT phase. 18,57 We measured the pressure dependence of the Fe Kβ emission spectra for SrFe 2 As 2 , from which we know the pressure-induced change in the IAD values, corresponding to the magnetic moment. The results indicate a gradual decrease of the magnetic moment with pressure up to 11.8 GPa at 17 K and up to 15.6 GPa at 300 K. A similar trend has been observed in K x Fe 2−y Se 2 .…”
Section: A the Iad Values Local Magnetic Moment And Electron-electmentioning
confidence: 99%
“…The theory predicted the transition to the zero-magnetic moment at the cT phase. 18,57 We measured the pressure dependence of the Fe Kβ emission spectra for SrFe 2 As 2 , from which we know the pressure-induced change in the IAD values, corresponding to the magnetic moment. The results indicate a gradual decrease of the magnetic moment with pressure up to 11.8 GPa at 17 K and up to 15.6 GPa at 300 K. A similar trend has been observed in K x Fe 2−y Se 2 .…”
Section: A the Iad Values Local Magnetic Moment And Electron-electmentioning
confidence: 99%
“…Our previous work [13], based on first principles density functional theory calculations, showed that the pressure-driven T = 0K transition from OR-AFM to tetragonal (cT or T) can be understood as a 1 st -order enthalpic transition that occurs at a pressure we denote P H . Subsequent work [14,15], also based on first principles total energy calculations, proposed that the T -cT transition and anomalies in lattice parameters and elastic properties, observed experimentally at finite temperatures, can be interpreted as arising from proximity to T = 0K Lifshitz transitions, at pressures denoted as P L , wherein pressure-driven changes in lattice constants alter the Fermi surface topology in these materials. Finally, our work revealed the existence of a metastable OR-AFM phase that remains mechanically stable until it transitions discontinuously to the tetragonal phase at a pressure we denoted P M .…”
Section: Introductionmentioning
confidence: 99%